A 5000-year overview of the history of pain through ancient civilizations to modern pain theories - Matthieu Vincenot; Pierrick Poisbeau; Nikolas Morel-Ferland; Geneviève Dumas; Guillaume Léonard (PAIN Reports)
Abstract. Pain and its management have been a predominant issue since the dawn of humanity. Pain has been the subject of much controversy and has constantly evolved across societies. The objective of this review is to trace the historical evolution of the concept of pain through the ages and to attempt to understand how modern theories of pain represent a legacy of ancestral knowledge passed down from culture to culture. We conducted a comprehensive review of primary and secondary sources across 6 major historical periods, including Pre-history, Antiquity, the Middle Ages, the Renaissance, the Modern, and Contemporary eras, using academic databases, specialized libraries, and historical archives. Results shows that during ancient civilizations, the understanding of pain oscillated between religious beliefs and medical advances. Antiquity societies made significant contributions to the understanding of pain mechanisms and management. Contrary to popular belief, significant advances were made during the Middle Ages despite the important impact of religion on the era's conceptualization of pain. During the Renaissance, the influence of religion waned, and secular medicine made significant progress. The development of pain theories peaked in the 19th century with technological advances. Long considered an expression of internal suffering, pain has fascinated humanity throughout history. The way pain has been perceived, understood, and treated has changed greatly over the centuries. This historical scientific review allows us to keep in mind that the vision we have of pain in Western society is predominantly based on the concrete heritage of ancient civilizations.